Francesca Bonicalzi, Leggere Bachelard. Le ragioni del sapere (Altre Modernità, 2012)
Francesca Bonicalzi, Leggere Bachelard. Le ragioni del sapere (Milano, Jaca Book, 2007 ISBN 978-881-640-771-8) di  Marco Maurizi